2022-RA-1023-ESGO Expression of P16 and Ki67 in cervical high grade squamous intraepithelial lesion in women up to 30 years old. (20th October 2022) - Rosin, Giovana Fontes; Magno, Valentino Antonio; Pessini, Suzana Arenhart
Abstract : Introduction/Background: Immunohistochemistry is a technique that evaluates the association of biomarkers with morphological changes, offering a higher level of reproducibility, sensitivity, and specificity in the diagnosis of many neoplasms, with p16 associated with high-risk HPV and ki-67 with cell multiplication. The aim is to determine the expression of p16 and Ki67 in high-grade intraepithelial lesions in patients aged 30 years or younger and correlate clinical outcome. Methodology: Retrospective cross-sectional study, that analyzes women diagnosed with HSIL treated at the gynecology outpatient clinic of the University Hospital. Demographic and clinical data and follow-up were collected from the hospital records. Descriptive analyses were expressed by measures of central tendency and dispersion. To identify possible associations between qualitative variables, the chi-square test was used. Spearman correlation were conducted between the variables of interest. Results: The average age of the participants was 27 years, and the majority were healthy 49 (72.1%) and non-smokers 47 (69.1%). Only 21 (30.9%) of them had completed high school and 5 (7.4%) had higher education. Considering the anatomopathological characteristics, most participants had cervical intraepithelial neoplasia (CIN) III (77.9%) and, to a lesser extent, cervical intraepithelial neoplasia (CIN) II (22.1%). Practically all were positive for P16INK4a and Ki67 (97.1% and 98.5%, respectively), and 65 (95.6%) were discharged from the outpatient clinic, with only 1 (1.5%) relapsed during follow-up. The analyzes did not show correlations between any of the variables of interest (e. g. age, age less than or equal to 30 years, parity, smoking and immunosuppression), with the outcomes studied (positive P16INK4a and Ki67) (Spearman correlations, p>0.05 for all the analyses). Furthermore, P16INK4a and Ki67 were positively related (Spearman, ρ=0.702, p≤0.001). Conclusion: It was not possible to prove that the use of biomarkers helps in the diagnosis and prognosis of precursor lesions in women aged up to 30 years.